Shakespeare and his authors : critical perspectives on the authorship question - Leahy, William, 1959- (Continuum, 2010)
The Shakespeare Authorship question - the question of who wrote Shakespeare's plays and who the man we know as Shakespeare was - is a subject which fascinates millions of people the world over and can be seen as a major cultural phenomenon. However, much discussion of the question exists on the very margins of academia, deemed by most Shakespearean academics as unimportant or, indeed, of interest only to conspiracy theorists. Yet, many academics find the Authorship question interesting and worthy of analysis in theoretical and philosophical terms. This collection brings together leading litera.